Perceptions and practices of COVID-19 protective measures among the general public of North India - Tuhina Rastogi; Shally Awasthi; Ranjan Khare; Mahesh Prasad; Gulshan Sami; Vijay Kumar Verma (Elsevier, 2022)
Background: India has a high COVID-19 burden. The Indian government responded to the pandemic by mandating its population to adhere to certain Protective Measures (PMs). Compliance to these PMs depends on their acceptability and adaptability among the general public. Aims: To explore the perceptions and practices of COVID-19 related PMs among the general public of North India. Methods: Qualitative study in four administrative districts (Lucknow, Etawah, Patna and Darbhanga) of North India. Two urban and two rural districts were purposefully selected. Audio in-depth interviews (IDIs) were conducted with healthy caregivers of children (2-59 months). Data was managed using Atlast Ti and analyzed using conventional content analysis. Results: From July-Sep 2020, 60 IDIs were conducted; 36.6% (22/60) were females and 26.6% (16/60) had below primary education. Respondents concurred that most people in their society flouted the recommended PMs. The reasons for poor/non-compliance with PMs were: perceived poor susceptibility to illness, perceived less severity of COVID-19 and low perceived benefits of complying with the PMs. Respondents opined that COVID-19 is less prevalent in rural areas and among the educated population. Most respondents were aware of the recommended PMs and opined that these must be followed, however subjective norms, social norms and behavioral intentions negatively impacted compliance. Conclusions: Since there was poor community perception of susceptibility to COVID-19 as well as poor perceived severity, the community did not understand the benefits of adhering to the recommended PMs. Therefore, future health communication strategies must take these into account to increase the possibility of success.